Analysis of Islamic Law and Positive Law on Marriage Due to Violation of Moral Norms - Muhammad Sya’ban Siregar; Syafruddin Syam; Heri Firmansyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Violations of moral norms often have significant social impacts, one of which is marriage which is carried out as a form of resolving moral conflicts in society. This article aims to analyze marriage due to violations of moral norms in Pematang Siantar City based on the perspective of Islamic law and positive law in Indonesia. In Islamic law, marriage is often considered a solution to normalize social relations after the occurrence of a violation, although there are requirements and principles that must be met. Meanwhile, positive law in Indonesia emphasizes the formal legality aspect and does not explicitly regulate the obligation to marry in such situations. This study also discusses various social implications that arise as a result of this phenomenon, such as social pressure on the individuals involved, as well as its impact on household stability. Using a normative-juridical approach, this article reviews how the two legal systems view this phenomenon, as well as providing an overview of the integration efforts between religious, legal, and cultural values in resolving this problem. The results of the analysis show that a comprehensive approach is needed to handle marriage cases due to violations of moral norms, in order to ensure justice for all parties involved.